Transverse testicular ectopia with scrotal hypospadias but without inguinal hernia – Case report of a rare association - Kajal, Pradeep (Int J Surg Case Rep, 2017)
Transverse testicular ectopia is an extremely rare anomaly, in which both the testis migrate towards the same hemiscrotum through the same inguinal canal. It is usually associated with other abnormalities such as persistent Mullerian duct syndrome, true hermaphroditism, inguinal hernia, pseudohermaphroditism, and scrotal anomalies; the association with inguinal hernia being the commonest. We, here, report a case of transverse testicular ectopia in a 12 years old boy having the ectopic testis in contralateral hemiscrotum without any inguinal hernia but having scrotal hypospadias with severe chordee. The diagnosis was made on clinical examination and confirmed on ultrasonography. Trans-septal orchiopexy was done for ectopic testis and hypospadias and chordee were managed by staged repair.